Perceptual Transparency From Cast Shadow. (May 2019) - Kawabe, Takahiro
This study examined how a shadow contributes to the perception of a transparent surface. As stimuli, we used computer graphics images in which a transparent surface with a color-mosaic pattern casts a shadow onto a background surface. We manipulated two parameters: (a) the spatial heterogeneity of the transmittance of the transparent surface and (b) the size of the light source shining on the transparent surface and its background. The latter parameter determined the blurriness of shadows. Observers judged whether the stimulus image contained a transparent surface or not. We found that the proportion of reports identifying a transparent surface was dependent on both parameters we tested. Specifically, a high spatial heterogeneity of transmittance decreased the proportion of reports of a transparent surface; this was possibly because globally defined X-junctions, which were one of the cues to perceptual transparency, perceptually broke down. On the other hand, blurred shadows were effective even when the global X-junctions were not effective. Locally defined X-junctions only moderately contributed to perceptual transparency. The results indicate that in addition to global and local X-junctions, blurred shadows are image features that elicit the perception of transparency from a cast shadow. A large individual difference as to which information each participant used as a cue to perceptual transparency was also discussed.